PENDUGAAN MODEL PERAMALAN HARGA BERAS PADA TINGKAT GROSIR - Sukiyono, Ketut; Rosdiana, Rosdiana (Badan Penerbitan Fakultas Pertanian, Universitas Bengkulu, 2018)
This research is aimed at examining the best forecasting model for riceprice at wholesaler price. Monthly data of ricefrom 2010:1 –2017:12 are used for this research and three trend model, i.e.,MA, Decomposition and Single Exponential Smoothing are applied in which the selection of the best model is based on the lowest value of MAPE, MAD, and MSE or MSD. This research finds that the best forecasting model is MA(2).